Copy-number of broad host-range plasmid R1162 is regulated by a small RNA. - Kim, K (1986)
We have shown previously [Kim, K. and Meyer, R.J. (1985) J. Mol. Biol. 185,755-767] that copy-number of the broad host-range plasmid R1162 is controlled by the amounts of two proteins, encoded by cotranscribed genes comprising a region of the plasmid called RepI. We have now demonstrated that expression of RepI is negatively regulated by a 75 base RNA that is complementary to a segment of the RepI message. Increased intracellular amounts of RNA molecules that include this segment relieve the inhibition of RepI gene expression, suggesting that the target for regulation is the mRNA itself. A mutation decreasing the amount of the 75 base RNA results in elevated plasmid copy-number. Thus, consistent with our previous observations, regulation of the expression of the RepI genes is a factor in controlling plasmid copy-number.